THE PYRAMID OF GLOBAL ENVIRONMENTAL MOVEMENT: CASE STUDY OF THE IMPACT GRETA THUNBERG IN INDONESIA - Robertua, Verdinand; Putri Rahayu, Mayra; Yandy Zefanya Pangihutan, Afri; Peron Abda, Eunitania (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2024)
This study extends the Pyramid of Digital Activism conceptualized by George and Leidner (2019) to the global environmental movement, using Greta Thunberg as a case study. The proposed framework categorizes digital activists into three tiers: gladiators, transition, and spectators. The gladiator level is characterized by eco-celebrity status, confrontative nature, and the utilization of digital activism. Greta Thunberg exemplifies this tier through her confrontative activism, strategic use of digital media, and global recognition as an eco-celebrity. This research explores Thunberg's impact on environmental politics in Indonesia, highlighting how her digital activism has galvanized a new generation of eco-activists and influenced policy discussions. By leveraging social media, Thunberg has transcended geographical barriers, demonstrating the potential of digital activism to foster significant environmental advocacy and policy change. The study concludes that the new Pyramid of Global Environmental Activism framework provides a robust model for understanding the dynamics and impact of digital activism within the environmental movement. Keywords: Global Environmental Movement, Greta Thunberg, Indonesia, Digital Activism, Case Study